Aktivitas Antibakteri Ekstrak Etanol Biji Keluak (Pangium Edule) Terhadap Bakteri Salmonella Typhi - Jatmiko, Ricko Arie; Milliana, Alvi; Indradmojo, Christyaji (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background: Typhoid fever often occurs in various countries in the world and generally occurs in countries with low levels of cleanliness. Typhoid fever is a systemic disease caused by Salmonella typhi bacterial infection. The main therapy for typhoid fever is antibiotics. The challenge of using synthetic antibiotics nowadays is the emergence of side effects of resistance. One of the plants that can be used as an antibacterial is extract of keluak seed (Pangium edule). This study aims to determine the antibacterial activity of keluak seed (Pangium edule) antibacterial extract on the growth of Salmonella typhi. This research is a quantitative type of experimental research with true experimental post-test control design). Method: The method used in this study used a qualitative phytochemical test and dilution of the tube. This study uses 6 concentrations which are 5, 10, 15, 20, 25, and 30 mg/ml. Bacterial suspension was used as negative control and extract 100 mg/ml was used as positive control. Result: Based on the phytochemical test show that the seeds of the keluak seed (Pangium edule) contain alkaloids and terpenoids. The extract of keluak seed seed has a MIC at a concentration of 10 mg/ml and MKC 30 mg/ml. MKC data were analyzed by the KruskalWallis test (significance p = 0,000) with (coefficient correlation= -0,990) the relationship between the two variables is very strong. Conclusion: The extract keluak seed (Pangium edule) seeds can inhibit the growth of S. typhi bacteria.